HUBUNGAN ACTIVITY OF DAILY LIVING (ADL) DENGAN KUALITAS TIDUR PADA LANSIA DI PSTW KHUSNUL KHOTIMAH PEKANBARU - Yeni Rosdianti; Herlina Herlina; Oswati Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Elderly are very susceptible of diseases caused by the aging process which results in a decrease, organ function that affects the mental and psychosocial conditions. This research aimed to determine correlation between the activity of daily living (ADL) with quality of sleep in the elderly. This research descriptive correlation cross sectional design. This research was conducted in PSTW Khusnul Khotimah of Pekanbaru involving 49 respondents. The sampling method was simple purposive sampling. The measuring instrument used was a questionnaire of the Index Barthel and Pittsburgh Sleep Quality Index (PSQI) both of which are already standardized. The analysis used was univariate and bivariate by Fisher Exact Test. The result analysis univariate showed that the majority of respondents are in the category of elderly (60-74 years) (63.3%). 28 respondents were female (42.9%), and 36 respondents had elementary education (73.5%). The results of this study indicate that there a relationship between activity of daily living (ADL) with sleep quality in elderly p value (0.037 < α 0.05).Keywords: Activity of daily living (ADL), Elderly, Sleep quality